OBTAINING α,β - UNSATURATED KETONES (Scientific journal of the Fergana State University, 2025)
The article describes the synthesis of α,β-unsaturated ketones based on formalin, acetone, and methylethyl ketone by condensation, and the products of condensation of acetone-formaldehyde-ACF, methylethylketone-formaldehyde-MEKF, and furfural with acetone-FAM are presented. Benzaldehyde, furfurol as such, is widely used from several areas of the national economy of aldehydes, since the physicochemical properties of polymercompositional compounds obtained on their basis are distinguished by a very high level. Furfurol, which plays an important role in industry, is mainly derived from furfurol alone on an industrial scale, while furfurol is derived from plant-based, xylose, arabinose, sucrose, pentozanlartutgan, grass-growing, lichen, mosses, hornbeam, Hawthorn stem, Grasshopper bark, Mecca Marda, salmon, poxol, saw ball, ghazans, semichka stem, reeds and other plant waste in the process of producing furfurol.